A133: Initial Benchmarking of the Quality of Medical Care of Children and Adolescents with Lupus. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Zaal, Ahmad I.; Appenzeller, Simone; Harris, Julia G.; Silva, Marco F.; Lee, Jiha; Centeville, Maraisa; Liu, HaiMei; Pendl, Joshua D.; Huggins, Jennifer L.; Johnson, Anne; Silva, Clovis A.; Hermine, Brunner
Abstract : Background/Purpose: Recently, 26 quality indicators (QI) categorized into 9 domains for childhood‐onset systemic lupus erythematous (cSLE) have been developed based on international consensus and scientific evidence. QI are defined as minimum standards of medical care in support of optimal disease outcomes. The current level at which these QI are followed has not been well documented. Hence, the objective of this study is to assess the current quality of medical care received by patients with cSLE at tertiary pediatric rheumatology centers. Methods: Cross‐sectional data pertaining to the QI were acquired via chart review and analyzed collectively in 290 cSLE patients followed at four tertiary pediatric rheumatology centers—two in the United States and two in Brazil. Results: Adherence to the QI differed by QI domain, ranging from 41 to 100%. The QI domain with the highest adherence 100% was Laboratory Testing at the time of diagnosis, and the lowest domain 41% was Medication Management. The recommended kidney biopsies for newly diagnosed lupus nephritis were done in only 67% of the patients and 85% of the patients received at least one of the recommended vaccinations (Table1 ). Cardiovascular risks factors were discussed in 86% of cases when patient was 13 years or older. Adherence to the QI differences between countries and insurance status will be presented, supporting that the set of current QI are suitable for international use. Conclusion: Based on this initial benchmarking effort, the medical care of patients with cSLE at tertiary pediatric rheumatology centers is very good. Systematic planning and documentation of patient education on lifestyle modifications seems warranted and is expected to improve the self‐management skills of cSLE patients. Furthermore, increased focus on bone health, eye exams annually, and adequate vaccination of cSLE patients are areas to continue to monitor.